Good Faith, a Concept in Contract Law: Chasing a Mirage or a Miracle in Australian Context - Nazli, Ismail@Nawang; Nurhidayah, Abdullah; Fatimah, Kari (2015)
It is the aim of the article to provide a context for understanding the concept of good faith in Australia. Good faith is arguably the most controversial concept in the law of contract, nevertheless it gains recognition and continues to have an increasing influence on many types of contracts. In Australia, the concept of good faith was introduced by Priestley J in his obiter comments in Renard Constructions (ME) Pty Ltd v Minister for Public Works (1992). Although the concept of good faith is widely discussed, it is without a definitive guide in Australian contract law. Despite the absence of an underlying obligation of good faith in Australian contract law, the concept of good faith is relevant to Australian contract law.